Empirical Analysis on Price-Volume Relation in the Stock Market of China - Wei, Shih-Yung; Lin, Li-Wei; Yan, Surong; Zhu, Lu-jie (International Journal of Economics and Financial Issues, 2019)
In this paper, the Granger causality test is used to explore the price-volume relation of the Shenzhen Stock Exchange and the Shanghai Stock Exchange and the spillover effect during the consolidation and the bull market. The research results show that price occurs after trading volume regardless of the consolidation period or the period of entering bull market and spillover effect is not significant during consolidation. After the stock exchanges entered the bull market the spillover effect is rather significant because the causality existed between the Shenzhen Stock Exchange and the Shanghai Stock Exchange due to stock index change. Keywords: price-volume relation, spillover effect, causality JEL Classifications: C23, L25 DOI: https://doi.org/10.32479/ijefi.8198